Vitamin B6 Is Under a Tight Balance During Disease Development by Rhizoctonia solani on Different Cultivars of Potato and on Arabidopsis thaliana Mutants - Samsatly, Jamil; Bayen, Stéphane; Jabaji, Suha H. (Frontiers in Plant Science, 2020)
Vitamin B6 is well recognized as an essential antioxidant and plays a role in stress responses. Co-expression of plant and pathogen-derived vitamin B6 genes is critical during disease development of R. solani. However, little is known about the functionality of vitamin B6 vitamers during plant-R. solani interactions and their involvement in disease tolerance. Here, we explored the possible involvement of vitamin B6 during disease progression of potato cultivars of different susceptibility levels to R. solani. A distinct pattern of gene expression, pyridoxine (PN) concentration, and fungal biomass was found in the susceptible cv. Russet Burbank and tolerant cv. Chieftain. Accumulation of reactive oxygen species (ROS) in R. solani mycelia or plant tissues applying non-fluorescence or fluorescence methods was related to up-regulation in the vitamin B6 pathway and is indicative of oxidative stress. Russet Burbank was susceptible to R. solani, which was linked to reduced amounts of VB6 content. Prior to infection, constitutive PN levels were significantly higher in Russet Burbank by 1.6 folds compared to Chieftain. Upon infection with R. solani, PN levels in infected tissues increased more in Chieftain (1.7 folds) compared to Russet Burbank (1.4 folds). R. solani AG3 infection of potato sprouts in both cultivars significantly activates the fungal and plant vitamin B6 and glutathione-S-transferase (GST) genes in a tissue-specific response. Significant fold increases of transcript abundance of the fungal genes ranged from a minimum of 3.60 (RsolSG3GST) to a maximum of 13.91 (RsolAG3PDX2) in the surrounding necrotic lesion tissues (zone 1). On the other hand, PCA showed that the top plant genes STGST and STPDX1.1 were linked to both tissues of necrotic lesions (zone 2) and their surrounding areas of necrotic lesions. Functional characterization of Arabidopsis pdx1.3 mutants challenged with R. solani provided evidence into the role of the vitamin B6 pathway in the maintenance of plant tolerance during disease progression. Overall, we demonstrate that the production of vitamin VB6 is under tight control and is an essential determinant of disease development during the interaction of R. solani with potato cultivars.